Innovative knowledge: its origin, detachment and usage in production practice - Maceika, Augustinas; Jančiauskas, Bronius (Business: Theory and Practice, 2012)
The authors of this article established the goal to provide a research of the innovative knowledge usage situation in the practice, to analyse origin and concept of innovative knowledge, and to foresee the ways how to develop this phenomenon to have more benefits and effectiveness in the future. The authors of the article have carried out a number of studies, collected and analysed relevant information about innovative knowledge. Applied methods include a survey of scientific literature and other information sources, structural system analysis, a sociological inquiry of the industrial enterprises and public administration institutions personnel and experts evaluations. The analysis of the literature sources and inquiry results showed that for forward-looking company or institution it is important to begin improvement from the understanding of the key features and proper logical and practical its development. Such an essential feature would be the activities associated with the new, innovative, engineering, economic-social knowledge and its management. We have no doubt that business is impossible without a systematic, continu-ous creativity development, and creativity is impossible without innovative knowledge understanding and management.Article in Lithuanian. Inovatyvios žinios: jų kilmė, išskyrimas ir naudojimas gamybinėje veiklojeSantrauka. Šio straipsnio autoriai numatė tikslą – pateikti inovatyvių žinių kilmės ir sampratos analizę bei pamėginti plėtoti šį fenomeną siekiant gauti daugiau naudos ir efektyvumo ateityje. Straipsnio autoriai atliko keletą tyrimų, kurių metu buvo renkama ir analizuojama svarbi informacija apie inovatyvias žinias. Taikyti metodai – mokslinės literatūros ir kitų informacinių šaltinių tyrimas, struktūrinė sisteminė analizė, pramonės įmonių ir viešojo administravimo įstaigų personalo sociologinis tyrimas ir ekspertinis vertinimas. Iš literatūros šaltinių ir tyrimo rezultatų matyti, kad inovatyvių žinių srityje tobulinimą svarbu pradėti nuo savo įmonės gamybinės veiklos savybių supratimo ir tinkamo loginio bei praktinio jų plėtojimo. Įmonės veikla visada susijusi su inovatyviomis inžinerijos, ekonominio-socialinio pobūdžio žiniomis ir jų valdymu. Neabejojame, kad verslas neįmanomas be sistemingo, nuolatinio kūrybiškumo plėtojimo, o kūrybiškumas neįmanomas be inovatyvių žinių supratimo ir valdymo.Reikšminiai žodžiai: inovacijos, inovatyvumas, inovatyvios žinios, žinių valdymas, personalo vadyba.